Persamaan Differensial Parsial Difusi Homogen pada Selang , dengan Kondisi Batas Dirichlet dan Neumann - Rukmono Budi Utomo (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2016)
This paper examines the Partial Differential Equations (PDP) Homogeneous Diffusions on the interval , with Dirichlet and Neumann boundary conditions. Research done by understanding in advance of the general form of differential equations homogeneous diffusions without boundary conditions and find solutions completion. Once the research is done by introducing a common form PDP Diffusions Homogeneous with Dirichlet and Neumann boundary conditions and their completion. In this paper also included examples of the application of PDP Heat homogeneous for both types of the boundary conditions and the analysis.